Evaluating School Connectedness of Students with Emotional and Behavioral Disorders. Issue 3 (24th June 2019) - Marsh, Robbie Jordon; Higgins, Kyle; Morgan, Joseph; Cumming, Therese M; Brown, Monica; McCreery, Michael
Abstract: School connectedness is the extent to which a student feels that adults and peers at school care about his or her overall well-being. Students with emotional and behavioral disorders (EBD) may experience difficulty with developing high levels of school connectedness, which may lead to engagement in health-risk behaviors. The purpose of this study was to determine the levels of school connectedness of students with EBD and compare them with their general education peers. A questionnaire was created for this study with participants attending elementary, middle, and high schools. The results of the analysis indicated that of the four factors of school connectedness (that is, school bonding, school attachment, school engagement, and school climate), the students with EBD reported significantly lower levels of school bonding than did their general education peers. The results indicate that students with EBD experience school differently than their general education peers, particularly in terms of school bonding.